LITERATURE REVIEW ON DEVELOPMENT OF MATHEMATICS HIGHER ORDER THINKING SKILLS (HOTS) ASSESSMENT INSTRUMENTS - Rarri Bian Ryandi; Diah Dwi Santri (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
Higher Level Thinking Ability (HOTS) is the ability of students to interpret their knowledge in solving a problem through the process of analysis, evaluation and creating ideas from the problems presented. This study aims to identify the development of a Mathematics Higher Order Thinking Skills (HOTS) assessment instrument. This review research uses bibliometric methods and a qualitative approach in reviewing journals in 2019-2023. Based on the results of the analysis, it shows that the development of the HOTS instrument was carried out based on the questions available at school which were less varied, the questions were still at the comprehension stage, teachers did not yet understand how to make HOTS questions, students' abilities. One form of assessment developed is test questions with multiple choice instrument types, descriptions and authentic assessments. The test questions developed pay attention to HOTS characteristics such as paying attention to HOTS indicators, KKO, mathematical problems and stimuli, as well as Bloom's taxonomy.